Penerapan Vitalpac Early Warning Scoring dan Early Warning Scoring terhadap Perburukan Pasien Akibat Access Block - Sensi, Gervasius Nong; Ristonilassius; Stevani Basry; Fitri Ch. Barus (Journal of Telenursing (JOTING), 2025)
This study aims to determine the effectiveness of the implementation of VitalPac Early Warning Scoring (ViEWS) and Early Warning Scoring (EWS) on patient deterioration due to access block in the ER. The research method used is quantitative descriptive with the research design being observational analytic through a prospective approach. The results of this study indicate that through the Spearman's rho test, the p-value of ViEWS was 0.000 <0.05. In conclusion, ViEWS is a tool used to make very good and accurate observations of patient deterioration due to access block in the ER than EWS. Keywords: Early Warning Scoring (EWS), Patient deterioration, VitalPac Early Warning Scoring (ViEWS